Arab spring, Libyan winter - Prashad, Vijay (Oakland, CA : AK Press, 2012)
Discusses the wave of popular rebellion against governments in Arab nations during the Spring of 2011. This brief, timely analysis situates the assault on Libya in the context of the winds of revolt that swept through the Middle East in the Spring of 2011.
Includes index.
Keywords: Arab Spring, 2010-; Revolutions; Libya -- History -- Civil War, 2011-; Arab countries -- Politics and government -- 20th century